2010
DOI: 10.1016/j.transproceed.2010.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Oxygen Persufflation Increases ATP Levels as Shown by Nuclear Magnetic Resonance

Abstract: Background-Islet transplantation is a promising treatment for type 1 diabetes. Due to a shortage of suitable human pancreata, high cost, and the large dose of islets presently required for long-term diabetes reversal; it is important to maximize viable islet yield. Traditional methods of pancreas preservation have been identified as suboptimal due to insufficient oxygenation. Enhanced oxygen delivery is a key area of improvement. In this paper, we explored improved oxygen delivery by persufflation (PSF), ie, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Our research group is currently studying PSF of the pancreas to parallel our concurrent interests in pancreas HMP [89; 91] and have recently published several works on A-PSF of porcine pancreata for the purposes of improving whole organ and islet quality [78; 79]. In one study [79], human and porcine pancreata were preserved using TLM or A-PSF at 4°C. A-PSF was performed via the superior mesenteric artery and either the splenic artery (human) or the celiac trunk (pig).…”
Section: Whole Organ Persufflationmentioning
confidence: 99%
“…Our research group is currently studying PSF of the pancreas to parallel our concurrent interests in pancreas HMP [89; 91] and have recently published several works on A-PSF of porcine pancreata for the purposes of improving whole organ and islet quality [78; 79]. In one study [79], human and porcine pancreata were preserved using TLM or A-PSF at 4°C. A-PSF was performed via the superior mesenteric artery and either the splenic artery (human) or the celiac trunk (pig).…”
Section: Whole Organ Persufflationmentioning
confidence: 99%
“…Many factors contribute to islet yield and viability including donor related parameters, pancreas procurement and preservation methods [812], and especially the islet isolation process itself. Many islets are never retrieved during isolation [13] or are irreversibly damaged along the way [1416].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, shorter cold ischaemic time associates with better islet yields (White et al 2001). Transport using a two-layer method where the pancreas rests on a substrate in the top layer of a perfluorocarbon ''bath'' appears to give slightly improved outcomes (Scott et al 2010a) and showed promising results in pancreata from humans (Scott et al 2010b). …”
Section: Pancreas Perfusion and Transport Factorsmentioning
confidence: 99%